Invisible victims : homelessness and the growing security gap - Huey, Laura (University of Toronto Press, 2012)
"Invisible Victims presents the first comprehensive, integrated study of the risks faced by homeless people and their attempts to find safety and security in often dangerous environments. Huey draws not only on current debates on security within criminology, but also on a decade's worth of her own field research on the victimization and policing of the homeless. A theoretically and empirically informed examination of the myriad issues affecting the homeless, Invisible Victims makes a compelling case for society to provide necessary services and, above all, a basic level of security for this population."--